Dinâmica climática e as chuvas na região da Zona da Mata, Nordeste do Brasil - Pereira, Michaell Douglas Barbosa (2018)
The northeastern region of the Zona da Mata has great importance in the national context. It was in this sector that started the Brazilian colonization, in addition to the first economic cycles. This is one of the most densely populated regions of Brazil (IBGE, 2010) and it is an area that offers high levels of rainfall, being a striking feature of this region, however, little studied. This work has as theoretical-methodological basis the technique of "Rhythmic Analysis" of Monteiro (1971). This technique is a method of rhythm research therefore; climate allows understanding the usual succession and exceptional atmospheric states, and, it is still essential for a climate characterization with emphasis on regional atmospheric circulation. Before this, this scientific work seeks to contribute to the understanding of the climatology of the Zona da Mata by identify the participation of air masses and atmospheric systems operating in this area, as well as his reflections on variation of climate elements, especially rainfall. For this, was used a temporal scale of meteorological data from 1995 to 2016. These reports refer to 12 meteorological stations that are of the National Institute of Meteorology (INMET). Rhythmic Analysis requires a choice of standard years, therefore, opted for the application of the Quantis technique to the classification of annual rainfall totals. As result, can be mentioned it first that the year 2000 was considered Standard Year very rainy, 2002 was considered Normal Standard Year and 2016 became the very dry Standard Year. In second place, this research sought to identify possible relationships between the occurrence of El Niño and La Niña phenomena, and, positive and negative Dipolo with rainfall recorded in Zona da Mata, thus, was identified a strong relationship between rainfall in the study area and the occurrence of El Niño and La Niña. With regard to the positive and negative Dipolo, the number of occurrences of this phenomenon was insufficient to establish possible conclusions. Third, based on rainfall, was subdivided the Zona da Mata into three sub-sectors: Center-North, South and Far South. Lastly, the frequency, intensity and sector in which air masses and atmospheric systems operate in the Zona da Mata were successfully identified, these data were also represented spatially through maps.